OPTIMALISASI PENGGUNAAN EFEK CHROMA KEY PADA VIDEO EDITING MENGGUNAKAN METODE HALF CIRCLE LAYER GREEN SCREEN - Pradhana, Faisal Reza; Al Fatta, Hanif (Politeknik Sawunggalih Aji, 2016)
Chroma key is a special effect on video editing, used for compositing (layering) two images or video streams together based on chroma range. The technique has been used heavily in many fields to remove a background from a subject or videos. A color range in the foreground footage is made transparent, allowing separately filmed background footage or a static image to be inserted into the scene. Chroma key effect particulary used at video games, newscasting and modern movies. This research focused on chroma key effect optimization by modifying the shape of a greenscreen background in order to take pictures from different angles in the same time Keyword: Chroma key, Greenscreen, Special effect